O pensamento neoconservador em política externa nos Estados Unidos - Teixeira, Carlos Gustavo Poggio (2007)
The end of the Cold War led to a reorientation of the basis of the American conservative thought in foreign policy, in general, and of neoconservatism in particular. For the last one, emerged in the mid 1970´s, and which defined itself in opposition to communism, the demise of the Soviet Union was a blow that many analyses, including among its most prominent spokesmen, considered mortal. The events of September 11th, 2001 proved that these evaluations were mistaken and reinforced the proposition of this research that the neoconservative thought in foreign policy is not a mere configuration of transient opinions, but a coherent set of ideas, distinct of others approaches within the American debate. By using a number of writings of its participants, this research aimed to identify the elements composing the neoconservative thought in foreign policy, without ignoring the historical context s influences over it. Thus, this work offers an original timeline of this thought, as well as it identifies its basic themes present in some way since its conception. The research also intended to situate the neoconservative thought in foreign policy within the wider international relations debate, basing on classical theoretical approaches of the discipline, in order to demonstrate that neoconservatism possesses such a combination of elements that hinders its categorization under any of these approaches, requiring a separate theoretical elaboration that takes into consideration its expression as a typically American phenomenon